Reply to the letter to the editor ‘Man against machine: diagnostic performance of a deep learning convolutional neural network for dermoscopic melanoma recognition in comparison to 58 dermatologists’ by H. A. Haenssle et al. - Hänßle, Holger; Müller-Christmann, Christine; Uhlmann, Lorenz (Annals of oncology, 2019)
Thank you for the opportunity to describe in more detail the methodology of our study [1].
Gesehen am 28.10.2019